GAMBARAN IT RATIO PADA NEONATUS DENGAN RISIKO SEPSIS DI RSIA HERMINA CIPUTAT - Heru Setiawan Setiawan; Tri Prasetyorini Prasetyorini; Husjain Djajaningrat Djajaningrat (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Immature / total neutrophil (IT Ratio) is the ratio between the young and the total neutrofi neutrophils in peripheral blood smear preparations. Sepsis in neonates is a systemic inflammatory response syndrome that occurs as a result of an infection that can be caused by bacteria, viruses, fungi or parasites. Sepsis in the neonate can result in death, but the symptoms are non-specific that require fast and accurate diagnosis early. Increased IT Ratio can be used asan early detection of sepsis in neonates because of neutrophils is a non-specific immune response which first appeared in the process of infection (sepsis).The design method observational cross-sectional study with the aim to describe the IT Ratio in neonates with sepsis risk on Hermina Mother and Child Hospital,Ciputat. This study is based on literature data and medical records of patients who carry out checks on Hermina Mother and Child Hospital, Ciputat, from July to October 2015. The results of the secondary data on 80 patients who had sepsis risk gained an average age infants IT checks Ratio 1.7 days, the average maternal gestational age 38.3 weeks, an average of the results of IT Ratio 0.09, which affected risk factors for the mother experienced premature rupture of the frequency distribution of 2.5%, kemih1,2% tract infection, amniotic fluid hijau1,3%. By sex obtained group sex male 3 patients (3.6%) were the result ofincreased IT ratio, whereas female gender group 1 patients (1.3%) Conclusion: The increased IT Ratio> 0.2 (sepsis) of 4 patients 5.0% and for IT normal Ratio <0.2 as many as 76 patients 95.0%. IT ratios can be used for early detection of sepsis in neonates.